Research on Digital Monetary and Financial Supervision from the Perspective of Digital economy - Jin, Tianhao; Ran, Xiangdong (Transactions on Social Science, Education and Humanities Research, 2024)
In the context of the digital economy, digital currency has always been one of the hotly discussed topics among scholars. This article takes digital currency financial supervision as the research object and explores its current development trend, which is of great innovative significance. Through research, we found that digital currency has its own unique concept, but it is also easily confused with concepts such as virtual currency and electronic currency. Secondly, on the basis of examining the experience of foreign countries in digital currency financial supervision, it is analyzed that digital currency financial supervision has difficulties in cross-border supervision, imperfect supervision systems and frequent terrorist financing phenomena. It urgently requires the joint efforts of multiple subjects, socialized co-governance and governance. Strengthen international exchanges and cooperation to better deal with this problem.